Aspek Imunobiologik Fagositosis dan Penyakit - Marsetyawan HNE Marsetyawan HNE (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 1983)
This article describes the process and mechanism of phagocytosis, especially their immunological aspects. Phagocytosis is one of the body's second line of defence against foreign particles, e. g. infectious and non-infectious material. The macrophage system, mononuclear and polymorphonuclear cells are responsible for phagocitizing and processing those particles, moreover they serve the processed material to the specific immunocompetent system.In addition CO the normal mechanism of phagocytosis, this article describes some disturbances which interfere with each step of phagocytosis as chemotaxis, opsonization and intracellular killing; this inadequacy results as a certain disease.Key Words: mononuclear phagocyte system - non-specific immune response - inflammation - receptor of the phagocyte cell - opsonin